Googling Cesarean Section: A Survey on the Quality of the Information Available on the Internet. Issue 1 (March 2016) - Fioretti, B.T.; Reiter, M.; Betrán, A.P.; Torloni, M.R.
Abstract : ( BJOG. 2015;122(5):731–739) Although the World Health Organization stated in 1985 that there was no justification for cesarean section rates >10% to 15% anywhere in the world, rates have been rising steadily across the globe. Brazil has one of the highest rates of cesarean delivery (CD) in the world, with >50% of women delivered by cesarean section in 2010.